ADVANTAGES AND DISADVANTAGES OF DIRECT AND INDIRECT DRYING OF MERCANTILE GRAIN AND SEEDS - Babić, Mirko (Journal on Processing and Energy in Agriculture, 2020)
The question again arises as to how to dry certain types of agricultural grain products and seeds. Should it be indirect or direct? The reason for this is the occasional fires that occur in dryers. It is often and unprofessionally stated that the cause of fire is the use of a direct dryer. However, the causes of fires are multiple, and it is very rare because of the type of dryer. Two factors determine the differences between direct and indirect drying, and these are the nutritional and safety aspects. The ambition of this study is to clarify all the important differences between direct and indirect grain drying and to eliminate the established misconceptions on this issue. Drying of sunflower, oilseed rape and sorghum is especially delicate.
Keywords: grain dryer, fire, direct an indirect grain dryers, sunflower